KonservasiTransformasi Konservasi Gedung Perpustakaan Universitas: Studi Deskriptif tentang Praktik Pelestarian di Nigeria Gedung Perpustakaan untuk Pelestarian Informasi yang Efektif di Perpustakaan Universitas di Negara Bagian Enugu, Nigeria - Olanike Faith Mesagan; Hossana Twinomurinzi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
The study examined the conservation of library building for effective information preservation among university libraries in Enugu State, Nigeria. Descriptive survey with population of 325 library staff made up the study. The instruments for collecting data is questionnaire, analysed and presented in mean score, standard deviation as well as percentage and t-test. Results: conservation criteria for library building are clearing and cleaning of the library building, repair of roof, windows and doors, installation of fire and smoke alarm system, and the provision of enough security personnel around the building. Library buildings are being conserved to protect resources against natural disasters like flooding, and earthquake, against man-made disaster like fire, making library resources accessible, promote an end to wasteful use of non-renewable information resources, to encourages best practices in records management, and it provides an extremely attractive environment for the use of books. Findings on the adequacy level of policy and regulatory framework shows that disaster management, storage capacity for documentary resources, appropriateness of environmental conditions are to be consider in the library. The study recommended that the university library management should provide monitoring system for environmental condition, storage capacity for digital resources and disaster preventive measure in the library.